2014
DOI: 10.1016/j.psychres.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of alexithymia and mood on the categorization of nonverbal emotional vocalizations

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
1
5
0
2
Order By: Relevance
“…Results from a visual ERP study confirm that alexithymia is characterized by deficits in the early appraisal of angry faces: change and novelty are poorly detected in angry expressions [17]. Findings from an investigation on the categorization of nonverbal emotional vocalizations suggest that alexithymic deficits in emotion perception could occur across different sensory modalities [18].…”
Section: Introductionmentioning
confidence: 78%
“…Results from a visual ERP study confirm that alexithymia is characterized by deficits in the early appraisal of angry faces: change and novelty are poorly detected in angry expressions [17]. Findings from an investigation on the categorization of nonverbal emotional vocalizations suggest that alexithymic deficits in emotion perception could occur across different sensory modalities [18].…”
Section: Introductionmentioning
confidence: 78%
“…Ressaltamos a ausência de qualquer associação com os estados de humor e os fatores de alexitimia. Pesquisa prévia com universitários apontou correlações fracas entre o fator dificuldade em descrever sentimento da TAS-20 e o afeto negativo raiva (r s = -.28), entre o afeto negativo tristeza e o fator dificuldade em descrever sentimentos (r s = -.32) e entre o fator orientação externa e o afeto positivo contentamento (r s = -.22) (Bayot, et al, 2014). Outro estudo, com pacientes queixosos, apontou associações fracas e moderadas (r = -.20 -.51) entre os fatores da escala de alexitimia e os afetos positivos e negativos em geral (De Gucht, Fischler, & Heiser, 2004).…”
Section: Discussionunclassified
“…These findings on emotion perception in music are consistent with data from research on auditory emotion perception in speech and prosody. Previous studies examining healthy individuals and patients with mental disorders have revealed that alexithymia is related to a reduced capacity to recognize emotions from vocal expressions (Goerlich et al, 2011;Heaton et al, 2012;Bayot et al, 2014). Similarities of emotion expression in speech and music have been noticed early.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…In humans, non-verbal vocalizations of basic emotions are universally recognized (Sauter et al, 2010). Alexithymia was found to be associated with a reduced capacity to recognize emotions from vocal expressions in healthy individuals and patients with mental disorders (Goerlich et al, 2011;Heaton et al, 2012;Bayot et al, 2014but see Swart et al, 2009, for null results).…”
Section: Introductionmentioning
confidence: 99%